(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In India, cataract-related blindness is a major social, economic, and medical burden as well as a major cause of human illness. According to a survey conducted by the WHO and NPCB (National Programme for Control of Blindness), India has a backlog of over 22 million blind eyes and 12 million blind persons, 80.1% of whom are blind as a result of cataract. 3.8 million people worldwide experience cataract-related blindness every year. There are currently between 1.6 million and 1.9 million cataract procedures performed annually. In comparison to the current rate of 1.7 million cataract procedures per year, 5–6 million cataract operations will need to be conducted annually in order to address the backlog of cataract cases by the year 2000 and the rising incidence. With financial support from the World Bank, India is starting a new, long-term project to increase the capabilities of cataract surgery and service levels. The focus on implementing the cataract blindness programme in rural and tribal communities is a key component of this project.